Reading at Home: Comparison of Reading Ability Among Homeschooled and Traditionally Schooled Children. Issue 2 (17th February 2019) - Guterman, Oz; Neuman, Ari
Abstract : The homeschool framework differs significantly from the traditional school setting. Earlier research has shown differences between homeschooled and other children in language skills, but no study has examined how homeschooling is related to the acquisition of the different components of reading. The present research examined several reading skills, comparing these two groups. The findings indicated that the homeschooled children achieved lower results in reading comprehension, but not in listening comprehension. The homeschooled children were also found to have broader general knowledge than the other children did. The gap between the groups in reading was associated with lower levels of phonological awareness. These findings might be attributed to the different methods used to teach reading in the two frameworks.